TURBINE PERFORMANCE ANALYSIS IN THE HIGH PRESSURE HEATER (HPH) CONDITION NOT OPERATING - Caturwati, Ni Ketut; Yusuf, Yusvardi; Rosyadi, Imron (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
Turbines are one important component in a power plant. The function of the turbine is to utilize the potential energy contained in the steam which is then converted into kinetic energy by the nozzle, then the kinetic energy is converted again into mechanical energy in the turbine blade and shaft rotation. In a rankine cycle after the steam comes out of the Low Pressure Turbine (LPT), the steam will change in phase from gas to liquid by passing through the condenser. The condensate water is heated again through a Low Pressure Heater (LPH) until finally it is heated again to the High Pressure Heater (HPH) before entering the boiler. But whether the performance of the turbine if when the HPH is not operating will decrease. In this study, an efficiency calculation will be carried out between the condition of the HPH operating and the condition of the HPH not operating, as well as finding coal consumption in both conditions. Based on the study, turbine efficiency did not show any significant difference between the condition of the HPH being in operation and the HPH not operating, that is 94.07% for the condition of the HPH to operate and 93.72% for the condition of the HPH not operating. While coal consumption at the time the HPH was operating was 164 Ton / h and at the HPH not operating was 170 Ton /h.